Global Marine Heatwaves Under Different Flavors of ENSO - Catherine H. Gregory; Camila Artana; Skylar Lama; Dalena León‐FonFay; Jacopo Sala; Fuan Xiao; Tongtong Xu; Antonietta Capotondi; Cristian Martinez‐Villalobos; Neil J. Holbrook (Geophysical Research Letters)
Abstract Marine heatwaves (MHWs) have caused devasting ecological and socioeconomic impacts worldwide. Understanding the connection of regional events to large‐scale climatic drivers is key for enhancing predictability and mitigating MHW impacts. Despite the reported connection between MHWs globally and El Niño–Southern Oscillation (ENSO), establishing statistically significant links between different types of ENSO events and MHWs remains challenging due to the limited duration of observational data. Here, we use 10,000 years of simulations from a Linear Inverse Model (LIM) to address this issue. Our findings reveal distinct connections between MHWs and ENSO, with diverging influences from different flavors of El Niño and La Niña events. In addition, under long‐lasting El Niño conditions, the likelihood of MHWs increases by up to 12‐fold in the Indian and Pacific Oceans. This study highlights the global connections between ENSO diversity and variations in MHW events.